A Mechanistic Study of Surfactants, Particles, and Polymers on Foam Stabilization. (April 2019) - Tiong, Adrian Chiong Yuh; Tan, Inn Shi; Foo, Henry Chee Yew
Abstract: Foam stabilization by mixtures of Bentonite, Xanthan Gum (XG) as stabilizers, and surfactants such as Sodium Dodecyl Sulfate (SDS) and Hexadecyltrimethyl Bromide (CTAB) were mechanistically investigated. Surface modification, adsorption properties and foaming characteristics of both surfactants were compared. Both possess dissimilar surface modification mechanisms namely the hydrophobic interaction mechanism for SDS and ion-pair mechanisms for CTAB. SDS generates foam of 21 % longer half-life and 17 % better foamability as compared to CTAB. Both Bentonite-stabilized and XG-stabilized SDS foam showed improvement of half-life of up to 10000 folds and 50000 folds. A reduction in foamability of up to 24% and 40% for Bentonite and XG respectively were observed. With increasing stabilizers concentration, viscosities across different shear rates and the elastic moduli (G') across different frequencies increase due to the increasing particles adsorption density on the air/water interface. Bentonite acts as a better synergist to SDS in foam formation as it has less viscosifying tendencies as compared to XG. It is also able to sufficiently improve SDS foam properties.